2008
DOI: 10.1177/1077801208329145
|View full text |Cite
|
Sign up to set email alerts
|

Battered Women Who Kill

Abstract: Mock jurors (N = 312) viewed a simulated trial involving a woman, charged with the murder of her abusive husband, entering a plea of not guilty by reason of self-defense. Expert testimony was varied using battered woman syndrome, social agency framework, or no expert testimony. Within expert testimony conditions, jurors were presented with opening and closing statements either including or not including instructions aimed at inducing empathy. Results indicate differences in gender and expert testimony for rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…This supported the hypothesis that increasing levels of empathy were associated with decreasing levels of stringency of punishment. The current findings also support the conclusions from the studies by Haegerich and Bottoms (2000) and Plumm and Terrance (2009), which both concluded that empathy plays a role when it comes to the decision making of jurors in court cases. In addition, it was found that increasing levels in each of the empathic subscales of perspective taking and empathic concern were associated with decreasing levels of stringency of punishment.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…This supported the hypothesis that increasing levels of empathy were associated with decreasing levels of stringency of punishment. The current findings also support the conclusions from the studies by Haegerich and Bottoms (2000) and Plumm and Terrance (2009), which both concluded that empathy plays a role when it comes to the decision making of jurors in court cases. In addition, it was found that increasing levels in each of the empathic subscales of perspective taking and empathic concern were associated with decreasing levels of stringency of punishment.…”
Section: Discussionsupporting
confidence: 80%
“…In other words, this study builds on the already established research that has highlighted the importance of empathy in jury decision making (e.g., Garvey, 2000;Haegerich & Bottoms, 2000;Plumm & Terrance, 2009;Sundby, 2003). However, it also expanded the current research by showing that individual differences in empathy among mock jurors affected their sentencing decisions.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations